2016
DOI: 10.12659/msm.895788
|View full text |Cite
|
Sign up to set email alerts
|

Microrna-199a-5p Functions as a Tumor Suppressor via Suppressing Connective Tissue Growth Factor (CTGF) in Follicular Thyroid Carcinoma

Abstract: BackgroundThe objective of this study was to explore the role of miR-199a-5p in the development of thyroid cancer, including its anti-proliferation effect and downstream signaling pathway.Material/MethodsWe conducted qRT-PCR analysis to detect the expressions of several microRNAs in 42 follicular thyroid carcinoma patients and 42 controls. We identified CTGF as target of miR-491, and viability and cell cycle status were determined in FTC-133 cells transfected with CTGF siRNA, miR-199a mimics, or inhibitors.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 33 publications
(31 reference statements)
0
20
0
2
Order By: Relevance
“…Our data are supported by the decreased expression of miR-199a-5p in keloid tissue compared with normal human skin 46 and the very recent finding that miR-199a-5p functions as a tumor suppressor in follicular cancer by suppressing CCN2. 47 Furthermore, the concomitant inhibition of expression of a-SMA and/or collagen 1(a1) is consistent with their CCN2 dependency in HSCs 33 but may also result from the regulation of other miR-199a-5p targets. Although our mechanistic data are consistent with decreased miR-199a-5p accounting for increased CCN2 expression during HSC activation, other studies have found miR-199a-5p expression to be increased in fibrotic livers or in activated HSCs.…”
Section: Discussionmentioning
confidence: 74%
“…Our data are supported by the decreased expression of miR-199a-5p in keloid tissue compared with normal human skin 46 and the very recent finding that miR-199a-5p functions as a tumor suppressor in follicular cancer by suppressing CCN2. 47 Furthermore, the concomitant inhibition of expression of a-SMA and/or collagen 1(a1) is consistent with their CCN2 dependency in HSCs 33 but may also result from the regulation of other miR-199a-5p targets. Although our mechanistic data are consistent with decreased miR-199a-5p accounting for increased CCN2 expression during HSC activation, other studies have found miR-199a-5p expression to be increased in fibrotic livers or in activated HSCs.…”
Section: Discussionmentioning
confidence: 74%
“…What's more, miR‐491 targets G‐protein‐coupled receptor kinase‐interacting protein 1 (GIT‐1), which blocked the activation of NF‐κB to attenuate cancer stem cell‐like properties of hepatocellular carcinoma . Besides, miR‐491 can also regulate its target genes, such as IGF2BP1, CTGF, TPX and Notch, functioning as tumour suppressor. Our study showed miR‐491‐5p suppressed the proliferation of human osteosarcoma cells and increased the cell apoptosis in vitro by targeting FOXP4 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that hsa-miR-199a-5p expression was significantly downregulated in PTC tissues and cells, and it inhibited the progression of PTC by downregulating snail family transcriptional repressor 1 (SNAI1) (23). A previous study demonstrated that hsa-miR-199a-5p was downregulated in tumor tissues obtained from patients with follicular thyroid carcinoma (FTC), and exhibited a negative association with its target, connective tissue growth factor (24). Therefore, hsa-miR-199a-5p may serve as a novel biomarker for the clinical management of thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 99%